Ceramic material with good temperature stability in different temperature environments and preparation

By doping strontium titanate in Bi0.5Na0.5TiO3 ceramics, a multi-element doped bismuth titanate-based ceramic material is solved, and the problem of deterioration of dielectric properties of ceramic materials at different temperatures is achieved under different temperature environments dielectric temperature stability and low loss effect.

CN119285351APending Publication Date: 2025-01-10XINING POWER SUPPLY CO OF STATE GRID QINGHAI ELECTRIC POWER CO +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411475799.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

It is difficult for ceramic materials to maintain good dielectric temperature stability at different ambient temperatures, especially due to the volatility of Na+ and Bi3+, the oxygen vacancy defect is activated, and the conductivity loss at high temperatures increases, limiting its application range.

Method used

Using multi-element doped bismuth titanate-based ceramic material, the capacitance temperature coefficient (TCC) of Bi0.5Na0.5TiO3 ceramics is improved by doping strontium titanate (SrTiO3) to achieve dielectric temperature under different temperature environments stability. The specific method includes using K0.05La0.05Ba0.054 (Bi0.5Na0.5)0.846Ti0.95Cr0.025Nb0.025O3 matrix material, doping SrTiO3 in different proportions, and preparing ceramic materials by traditional solid phase sintering method.

Benefits of technology

It realizes excellent capacitance temperature coefficient and dielectric temperature stability of ceramic materials under different temperature environments, meets the requirements of dielectric performance of electronic components at different operating ambient temperatures, and significantly reduces high-temperature dielectric loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005096073500000011
    Figure HDA0005096073500000011
  • Figure HDA0005096073500000012
    Figure HDA0005096073500000012
  • Figure HDA0005096073500000021
    Figure HDA0005096073500000021
Patent Text Reader

Abstract

The invention discloses a ceramic material with good temperature stability in different temperature environments and preparation, and relates to the field of electronic ceramic materials and electronic components. The strontium titanate doped sodium bismuth titanate-based ceramic material is obtained by taking multi-element doped sodium bismuth titanate-based ceramic as a matrix material and doping strontium titanate. A traditional solid-phase reaction method is adopted for preparation, and the preparation process comprises the steps of weighing, ball milling, pre-sintering, tabletting, glue discharging, sintering and electrode preparation. The invention has the following beneficial effects: strontium titanate is doped, excellent temperature coefficient of capacitance (TCC) is realized in sodium bismuth titanate-based ceramic under different temperature environments, and the ceramic material with excellent dielectric temperature stability is obtained, so as to meet the requirements of electronic components on dielectric properties of the ceramic material under different use environment temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic ceramic materials and electronic components, and in particular to ceramic materials with good temperature stability under different temperature environments and preparation methods. Background Art

[0002] With the continuous development and progress of electronic component technology, electronic ceramic materials are widely used in electronic components. At present, the materials commonly used in the field of electronic components can be roughly divided into three categories: polymer materials, ceramic materials, and composite materials. Among them, ceramic materials have good chemical stability at different temperatures and are easier to meet the application of electronic components at different ambient temperatures. However, the deterioration of the dielectric properties of ceramic materials at operating temperatures exceeding the ceramic Curie temperature limits their application at different ambient temperatures.

[0003] At present, the challenge is how to simultaneously achieve good dielectric temperature stability of ceramic materials at different ambient temperatures. Ceramic materials used at different ambient temperatures should have a good temperature coefficient of capacitance (TCC). In order to obtain good dielectric temperature stability at different ambient temperatures, such as strontium titanate (SrTiO3), sodium bismuth titanate (Bi 0.5 Na 0.5 TiO3), barium titanate (BaTiO3) and other ceramic materials have been extensively studied. 0.5 Na 0.5 TiO3 is a relaxor ferroelectric material with two dielectric anomaly peaks in its dielectric constant temperature spectrum. One dielectric anomaly peak corresponds to a temperature of 320°C (Tm), and the other dielectric anomaly peak corresponds to a temperature of 180°C (Ts). 0.5 Na 0.5 The special Ts-Tm RT phase transition temperature range of TiO3 can be made to show a wider dielectric temperature stability temperature range by means of element doping. 0.5 Na 0.5 TiO3-based ceramics have a relatively flat dielectric temperature spectrum, making them one of the candidate materials for applications in different temperature environments. 0.5 Na 0.5 Na in the sintering process of TiO3 ceramics + 、Bi 3+ The volatilization of Na will lead to the generation of defects such as oxygen vacancies. The defective carriers are activated at high temperatures, and the high-temperature conductivity loss increases sharply, which ultimately leads to a large high-temperature dielectric loss. 0.5 Bi 0.5+y TiO3-xNaTaO3 has good dielectric temperature stability. However, it only has good dielectric temperature stability at one reference temperature, which makes it difficult to use it at different ambient temperatures. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes to adopt SrTiO3 doping strategy to 0.5 Na 0.5 TiO3-based ceramics achieve excellent temperature coefficient of capacitance (TCC) at different ambient temperatures, and obtain ceramic materials with excellent dielectric temperature stability to meet the requirements of electronic components for dielectric properties of ceramic materials at different ambient temperatures.

[0005] The invention provides a ceramic material with good temperature stability under different temperature environments. The ceramic material is doped with strontium titanate to obtain a strontium titanate-doped sodium bismuth titanate-based ceramic material with multi-element doped sodium bismuth titanate as a matrix material.

[0006] The strontium titanate-doped sodium bismuth titanate-based ceramic material has a base material of K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 O3.

[0007] The composition formula of the strontium titanate-doped sodium bismuth titanate-based ceramic material is (1-x)K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 O3-xSrTiO3.

[0008] In the composition formula of the strontium titanate-doped sodium bismuth titanate-based ceramic material, the value range of x is: 0.05-0.4.

[0009] The strontium titanate-doped sodium bismuth titanate-based ceramic material is prepared from the following raw materials: anhydrous sodium carbonate, bismuth trioxide, titanium dioxide, anhydrous potassium carbonate, lanthanum trioxide, chromium trioxide, niobium pentoxide, barium carbonate and strontium carbonate.

[0010] The strontium titanate-doped sodium bismuth titanate-based ceramic material is prepared by a conventional solid phase sintering method, and the preparation process is: weighing → ball milling → pre-sintering → tableting → debinding and sintering → electrode preparation, specifically:

[0011] Weigh, calculate the molar amounts of anhydrous Na2CO3, Bi2O3, TiO2, anhydrous K2CO3, La2O3, Cr2O3, SrCO3, and Nb2O5 according to the required stoichiometric ratio and weigh them.

[0012] Ball milling, ZrO2 balls are used as grinding balls, and a certain mass of zirconia grinding balls are put into the nylon ball mill according to the mass ratio of 5:1. Then the weighed raw material powders are mixed and put into the nylon ball mill, and anhydrous ethanol is selected as the ball milling medium. After mixing, they are put into the planetary ball mill at a speed of 300r / min (about 25.98Hz). The forward and reverse intermittent ball milling method is adopted. The forward and reverse rotation direction is changed every 1h and the interval is 10min. The total ball milling time is about 14h.

[0013] Pre-sintering: Dry the wet powder after ball milling and mixing evenly in an oven at a constant temperature of 60-100°C for 2-6 hours to dry all the anhydrous ethanol. Put the dried mixed powder into a high-temperature box furnace, heat it from room temperature to 700-800°C at a heating rate of 5-15°C / min for 1-3 hours, and cool it naturally to obtain the pre-sintered powder.

[0014] Tableting: Weigh the powder obtained by pre-sintering to ensure that the thickness of the ceramic disc after sintering is basically consistent. Add 5-10wt% PVA solution to the weighed powder for granulation, then mix it evenly in a mortar and put it into a cylindrical mold with a diameter of 10mm, and press it into a disc with a diameter of 10mm and a thickness of about 1mm at a pressure of 5-15MPa for 5-15min.

[0015] Debinding and sintering: put the pressed disc into a high temperature furnace and heat it to 500-600℃ at a heating rate of 50-150℃ / h and keep it at that temperature for 1h, so that the PVA remaining in the disc can be decomposed and removed in the process of slow heating. Then heat the debinding disc from room temperature to 1100-1200℃ at a rate of 5-20℃ / min and keep it at that temperature for 3-5h to obtain a sintered ceramic disc.

[0016] Electrode preparation: polish both sides of the sintered ceramic with sandpaper until the surface is flat and smooth, brush conductive silver slurry on both sides, and solidify the slurry at 120°C. Finally, anneal the ceramic in a high-temperature furnace at a heating rate of 10°C / min to 600°C and keep it for 30 minutes.

[0017] The beneficial effect of the present invention is that: the present invention adopts multi-element doped sodium bismuth titanate-based ceramics as the matrix material, doped with strontium titanate, and realizes an excellent capacitance temperature coefficient (TCC) at different use environment temperatures in the sodium bismuth titanate-based ceramics, thereby obtaining a ceramic material with excellent dielectric temperature stability, achieving the effect of having good temperature stability under different temperature environments, and meeting the requirements of electronic components for the dielectric properties of ceramic materials under different use environment temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 For the present invention 0.95K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 Capacitance temperature coefficient of O3-0.05SrTiO3 ceramics under different temperature environments at a test frequency of 1kHz;

[0019] Figure 2 For the present invention 0.95K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 The temperature range corresponding to the temperature coefficient of O3-0.05SrTiO3 ceramic capacitor is less than ±15%;

[0020] Figure 3 The present invention 0.85K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 Capacitance temperature coefficient of O3-0.15SrTiO3 ceramics under different temperature environments at a test frequency of 1kHz;

[0021] Figure 4 For the present invention 0.85K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb0.025 The temperature range where the temperature coefficient of O3-0.15SrTiO3 ceramic capacitor is less than ±15%;

[0022] Figure 5 The present invention 0.75K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 Capacitance temperature coefficient of O3-0.25SrTiO3 ceramics under different temperature environments at a test frequency of 1kHz;

[0023] Figure 6 For the present invention 0.75K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 The temperature range where the temperature coefficient of O3-0.25SrTiO3 ceramic capacitor is less than ±15%;

[0024] Figure 7 The present invention 0.6K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 Capacitance temperature coefficient of O3-0.4SrTiO3 ceramics under different temperature environments at a test frequency of 1kHz;

[0025] Figure 8 For the present invention 0.6K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 The temperature range in which the temperature coefficient of O3-0.4SrTiO3 ceramic capacitance is less than ±15% corresponds to. DETAILED DESCRIPTION

[0026] To further illustrate the strontium titanate-doped sodium bismuth titanate-based ceramic material and preparation method provided by the present invention having good dielectric temperature stability under different temperature environments, the following implementation cases are used to illustrate the present invention, but are not used to limit the present invention.

[0027] Example 1, a ceramic material with good temperature stability under different temperature environments, with multi-element doped sodium bismuth titanate-based ceramic as the base material, the base material is K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 O3, doped with strontium titanate to obtain strontium titanate doped sodium bismuth titanate-based ceramic material. Its composition formula is: 0.95K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 O3-0.05SrTiO3;

[0028] The preparation method is as follows:

[0029] Weigh, calculate the molar amounts of anhydrous Na2CO3, Bi2O3, TiO2, anhydrous K2CO3, La2O3, Cr2O3, SrCO3, and Nb2O5 according to the required stoichiometric ratio and weigh them, and their masses are 2.13g, 9.46g, 7.74g, 0.33g, 0.77g, 0.19g, 0.75g, and 0.33g, respectively;

[0030] Ball milling: ZrO2 balls are used as grinding balls. A certain mass of zirconium oxide grinding balls are added according to a mass ratio of 5:1. The weighed raw material powders are mixed and put into a nylon ball mill. Anhydrous ethanol is selected as the ball milling medium. After mixing, the mixture is put into a planetary ball mill at a speed of 300 r / min (about 25.98 Hz). The ball milling method of forward and reverse rotation is adopted. The forward and reverse rotation direction is changed every 1 hour and the interval is 10 minutes. The total ball milling time is about 14 hours.

[0031] Pre-sintering: the wet powder after ball milling and mixing is dried in an oven at a constant temperature of 60-100°C for 2-6 hours to dry all the anhydrous ethanol, the dried mixed powder is placed in a high-temperature box furnace, heated from room temperature to 700-800°C at a heating rate of 5-15°C / min for 1-3 hours, and naturally cooled to obtain the pre-sintered powder;

[0032] Tableting: weigh the powder obtained by pre-sintering to ensure that the thickness of the ceramic disc after sintering remains basically the same; add a PVA solution with a mass fraction of 5 to 10 wt% to the weighed powder for granulation, then mix it evenly in a mortar and put it into a cylindrical mold with a diameter of 10 mm, and press it into a disc with a diameter of 10 mm and a thickness of about 1 mm at a pressure of 5 to 15 MPa for 5 to 15 minutes;

[0033] Debinding and sintering: Place the pressed disc in a high-temperature furnace and heat it to 500-600°C at a heating rate of 50-150°C / h and keep it at that temperature for 1 hour, so that the residual PVA in the disc can be decomposed and removed in the process of slow heating; then heat the debinded disc from room temperature to 1100-1200°C at a rate of 5-20°C / min and keep it at that temperature for 3-5 hours to obtain a sintered ceramic disc.

[0034] Electrode preparation: polish both sides of the sintered ceramic with sandpaper until the surface is flat and smooth, brush conductive silver slurry on both sides, and solidify the slurry at 120°C. Finally, anneal the ceramic in a high-temperature furnace at a heating rate of 10°C / min to 600°C and keep it for 30 minutes.

[0035] Through the above steps, a strontium titanate-doped sodium bismuth titanate-based ceramic material with good dielectric temperature stability under different ambient temperatures can be obtained. Figure 1 , 2 As shown, from Figure 1 It can be seen that the prepared strontium titanate-doped sodium bismuth titanate-based ceramic material has good dielectric temperature stability under different ambient temperatures; Figure 2 It can be seen that the temperature zones corresponding to the dielectric temperature stability of ceramic materials at operating temperatures of 100℃, 150℃, 200℃, 250℃, 300℃, and 350℃ reach 250, 252, 252, 278, 154, and 97 respectively, achieving good dielectric temperature stability under different temperature environments.

[0036] Example 2, a ceramic material with good temperature stability under different temperature environments, with multi-element doped sodium bismuth titanate-based ceramic as the base material, the base material is K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 O3, doped with strontium titanate to obtain strontium titanate doped sodium bismuth titanate-based ceramic material. Its composition formula is: 0.85K 0.05 La 0.05Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 O3-0.15SrTiO3; its preparation method is the same as that of Example 1, except that the raw material input ratios are different, and the masses of the raw materials anhydrous Na2CO3, Bi2O3, TiO2, anhydrous K2CO3, La2O3, Cr2O3, SrCO3, and Nb2O5 are 1.91g, 8.46g, 7.74g, 0.3g, 0.69g, 0.19g, 2.24g, and 0.33g, respectively;

[0037] Through the above steps, a strontium titanate-doped sodium bismuth titanate-based ceramic material with good dielectric temperature stability and high dielectric constant under different ambient temperatures can be obtained. Product performance Figure 3 , 4 As shown, from Figure 3 It can be seen that the prepared strontium titanate-doped sodium bismuth titanate-based ceramic material has good dielectric temperature stability under different ambient temperatures; Figure 4 It can be seen that the temperature zones corresponding to the dielectric temperature stability of ceramic materials at operating temperatures of 100℃, 150℃, 200℃, 250℃, 300℃, and 350℃ are 211, 221, 247, 291, 170, and 127 respectively, achieving good dielectric temperature stability under different temperature environments.

[0038] Example 3, a ceramic material with good temperature stability under different temperature environments, with multi-element doped sodium bismuth titanate-based ceramic as the base material, the base material is K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 O3, doped with strontium titanate to obtain strontium titanate doped sodium bismuth titanate-based ceramic material. Its composition formula is: 0.75K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025O3-0.25SrTiO3; its preparation method is the same as that of Example 1, except that the raw material input ratios are different, and the masses of the raw materials anhydrous Na2CO3, Bi2O3, TiO2, anhydrous K2CO3, La2O3, Cr2O3, SrCO3, and Nb2O5 are 1.68g, 7.47g, 7.74g, 0.26g, 0.61g, 0.19g, 3.73g, and 0.33g, respectively;

[0039] Through the above steps, a strontium titanate-doped sodium bismuth titanate-based ceramic material with good dielectric temperature stability and high dielectric constant under different ambient temperatures can be obtained. Product performance Figure 5 , 6 As shown, from Figure 5 It can be seen that the prepared strontium titanate-doped sodium bismuth titanate-based ceramic material has good dielectric temperature stability under different ambient temperatures; Figure 6 It can be seen that the temperature zones corresponding to the dielectric temperature stability of ceramic materials at operating temperatures of 100°C, 150°C, 200°C, 250°C, 300°C, and 350°C reach 156, 183, 182, 217, 187, and 171, respectively, achieving good dielectric temperature stability under different temperature environments.

[0040] Example 4, a ceramic material with good temperature stability under different temperature environments, with multi-element doped sodium bismuth titanate-based ceramic as the base material, the base material is K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 O3, doped with strontium titanate to obtain strontium titanate doped sodium bismuth titanate-based ceramic material. Its composition formula is: 0.6K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 O3-0.4SrTiO3; its preparation method is the same as that in Example 1, except that the proportions of raw materials input are different. The masses of the raw materials anhydrous Na2CO3, Bi2O3, TiO2, anhydrous K2CO3, La2O3, Cr2O3, SrCO3, and Nb2O5 are 1.35g, 5.97g, 7.74g, 0.21g, 0.49g, 0.19g, 5.96g, and 0.33g, respectively.

[0041] Through the above steps, a strontium titanate-doped sodium bismuth titanate-based ceramic material with good dielectric temperature stability and high dielectric constant under different ambient temperatures can be obtained. Product performance Figure 7 , 8 As shown, from Figure 7 It can be seen that the prepared strontium titanate-doped sodium bismuth titanate-based ceramic material has good dielectric temperature stability under different ambient temperatures. Figure 8 It can be seen that the temperature zones corresponding to the dielectric temperature stability of ceramic materials at operating temperatures of 100°C, 150°C, 200°C, 250°C, 300°C, and 350°C are 137, 160, 136, 205, 183, and 181, respectively, achieving good dielectric temperature stability under different temperature environments.

[0042] The above are preferred embodiments and comparative examples of the present invention, but the present invention should not be limited to the contents disclosed in the implementation examples. Therefore, any equivalent or modification completed without departing from the spirit disclosed in the present invention shall fall within the scope of protection of the present invention.

Claims

1. A ceramic material having good temperature stability under different temperature environments, characterized in that: The multi-element doped sodium bismuth titanate-based ceramic is used as a matrix material, and strontium titanate is doped to obtain a strontium titanate-doped sodium bismuth titanate-based ceramic material.

2. The ceramic material with good temperature stability under different temperature environments according to claim 1, characterized in that: The strontium titanate-doped sodium bismuth titanate-based ceramic material has a base material of K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 O3.

3. The ceramic material with good temperature stability under different temperature environments according to claim 2, characterized in that: The strontium titanate-doped sodium bismuth titanate-based ceramic material has a composition formula of (1-x)K 0.05 La 0.05 Ba 0.054 (Bi 0.5 Na 0.5 ) 0.846 Ti 0.95 Cr 0.025 Nb 0.025 O3-xSrTiO3.

4. The ceramic material having good temperature stability under different temperature environments according to claim 3, characterized in that: In the composition formula of the strontium titanate-doped sodium bismuth titanate-based ceramic material, the value range of x is: 0.05-0.

4.

5. The ceramic material with good temperature stability under different temperature environments according to claim 4, characterized in that: The strontium titanate-doped sodium bismuth titanate-based ceramic material is prepared from the following raw materials: anhydrous sodium carbonate, bismuth trioxide, titanium dioxide, anhydrous potassium carbonate, lanthanum trioxide, chromium trioxide, niobium pentoxide, barium carbonate and strontium carbonate.

6. A method for preparing a ceramic material having good temperature stability under different temperature environments, characterized in that: The preparation process of the strontium titanate-doped sodium bismuth titanate-based ceramic material is: weighing → ball milling → pre-sintering → tableting → debinding and sintering → electrode preparation, specifically: Weigh, calculate the molar amounts of anhydrous Na2CO3, Bi2O3, TiO2, anhydrous K2CO3, La2O3, Cr2O3, SrCO3, and Nb2O5 according to the required stoichiometric ratio and weigh; Ball milling: ZrO2 balls are used as grinding balls. A certain mass of zirconium oxide grinding balls are added according to a mass ratio of 5:

1. The weighed raw material powders are mixed and put into a nylon ball mill. Anhydrous ethanol is selected as the ball milling medium. After mixing, the mixture is put into a planetary ball mill at a speed of 300 r / min (about 25.98 Hz). The ball milling method of forward and reverse rotation is adopted. The forward and reverse rotation direction is changed every 1 hour and the interval is 10 minutes. The total ball milling time is about 14 hours. Pre-sintering: the wet powder after ball milling and mixing is dried in an oven at a constant temperature of 60-100°C for 2-6 hours to dry all the anhydrous ethanol, the dried mixed powder is placed in a high-temperature box furnace, heated from room temperature to 700-800°C at a heating rate of 5-15°C / min for 1-3 hours, and naturally cooled to obtain the pre-sintered powder; Tableting: weigh the powder obtained by pre-sintering to ensure that the thickness of the ceramic disc after sintering remains basically the same; add a PVA solution with a mass fraction of 5 to 10 wt% to the weighed powder for granulation, then mix it evenly in a mortar and put it into a cylindrical mold with a diameter of 10 mm, and press it into a disc with a diameter of 10 mm and a thickness of about 1 mm at a pressure of 5 to 15 MPa for 5 to 15 minutes; Debinding and sintering: the pressed disc is placed in a high-temperature furnace and heated to 500-600°C at a heating rate of 50-150°C / h and kept at that temperature for 1 hour, so that the PVA remaining in the disc is decomposed and removed in the process of slowly heating up; the debinded disc is then heated from room temperature to 1100-1200°C at a rate of 5-20°C / min and kept at that temperature for 3-5 hours to obtain a sintered ceramic disc; Electrode preparation: polish both sides of the sintered ceramic with sandpaper until the surface is flat and smooth, brush conductive silver slurry on both sides, and solidify the slurry at 120°C. Finally, anneal the ceramic in a high-temperature furnace at a heating rate of 10°C / min to 600°C and keep it for 30 minutes.